Acute-Phase Inflammatory Response to Single-Bout HIIT and Endurance Training: A Comparative Study - Felix Kaspar; Herbert F. Jelinek; Steven Perkins; Hayder A. Al-Aubaidy; Bev deJong; Eugene Butkowski (Hindawi Limited, 2016)
Objective. This study compared acute and late effect of single-bout endurance training (ET) and high-intensity interval training (HIIT) on the plasma levels of four inflammatory cytokines and C-reactive protein and insulin-like growth factor 1. Design. Cohort study with repeated-measures design. Methods. Seven healthy untrained volunteers completed a single bout of ET and HIIT on a cycle ergometer. ET and HIIT sessions were held in random order and at least 7 days apart. Blood was drawn before the interventions and 30 min and 2 days after the training sessions. Plasma samples were analyzed with ELISA for the interleukins (IL), IL-1β, IL-6, and IL-10, monocyte chemoattractant protein-1 (MCP-1), insulin growth factor 1 (IGF-1), and C-reactive protein (CRP). Statistical analysis was with Wilcoxon signed-rank tests. Results. ET led to both a significant acute and long-term inflammatory response with a significant decrease at 30 minutes after exercise in the IL-6/IL-10 ratio (−20%; p=0.047) and a decrease of MCP-1 (−17.9%; p=0.03). Conclusion. This study demonstrates that ET affects the inflammatory response more adversely at 30 minutes after exercise compared to HIIT. However, this is compensated by a significant decrease in MCP-1 at two days associated with a reduced risk of atherosclerosis.